Carbon Dots Mediated In Situ Confined Growth of Bi Clusters on g‐C3N4 Nanomeshes for Boosting Plasma‐Assisted Photoreduction of CO2. Issue 46 (10th October 2022) - Zhao, Xinyang; Li, Jun; Kong, Xiangguang; Li, Changchang; Lin, Bo; Dong, Fan; Yang, Guidong; Shao, Guosheng; Xue, Chao
Abstract: Synthesis of high‐efficiency, cost‐effective, and stable photocatalysts has long been a priority for sustainable photocatalytic CO2 reduction reactions (CRR), given its importance in achieving carbon neutrality goals under the new development philosophy. Fundamentally, the sluggish interface charge transportation and poor selectivity of products remain a challenge in the CRR progress. Herein, this work unveils a synergistic effect between high‐density monodispersed Bi/carbon dots (CDs) and ultrathin graphite phase carbon nitride (g‐C3 N4 ) nanomeshes for plasma‐assisted photocatalytic CRR. The optimal g‐C3 N4 /Bi/CDs heterojunction displays a high selectivity of 98% for CO production with a yield up to 22.7 µmol g −1 without any sacrificial agent. The in situ confined growth of plasmonic Bi clusters favors the production of more hot carriers and improves the conductivity of g‐C3 N4 . Meanwhile, a built‐in electric field driving force modulates the directional injection photogenerated holes from plasmonic Bi clusters and g‐C3 N4 photosensitive units to adjacent CDs reservoirs, thus promoting the rapid separation and oriented transfer in the CRR process. This work sheds light on the mechanism of plasma‐assisted photocatalytic CRR and provides a pathway for designing highly efficient plasma‐involved photocatalysts. Abstract : Herein, this work unveils a synergistic effect between high‐density monodispersed Bi/carbon dots (CDs) and ultrathin graphite phase carbon nitride (g‐C3 N4 ) nanomeshes for plasma‐assisted photocatalytic CO2 reduction reactions. The optimal g‐C3 N4 /Bi/CDs heterojunction displays a high selectivity of 98% for CO production with a yield up to 22.7 µmol g −1 without any sacrificial agent.